Merumuskan Visi, Misi, Fungsi Dan Tujuan Pembelajaran Pendidikan Agama Islam - Amirudin, Muhammad Faizul; Helandri, Joni; Lusia, Yuyun Cahyani; Melina, Vinny; Dinanti, Riska Destri (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
People must learn in order to grow as individuals, hence it is a basic human need. Not only may we learn in the classroom, but we can also learn from experiences we have outside of it, like tutoring, interacting with others, getting advice from others, and much more. Islam demands all of its followers men and women, young and old to pursue knowledge. Not only is knowledge of the hereafter sought, but also knowledge of this world. This journal was created using qualitative methodologies, including knowledge-gathering exploratory research. The information and resources needed for this study, which is qualitative in nature, were found through library research. The study's findings provide guidance on how to develop the goals, missions, and roles acquiring Islamic education in order to stay up to date with modern advancements.